Olfactory and gustatory dysfunctions as a clinical presentation of COVID-19 (Research, Society and Development, 2020)
This study aims to elucidate the evidence of olfactory and gustatory dysfunction and their characteristics in subjects diagnosed with COVID-19. Qualitative and descriptive research, based on an integrative literature review, carried out on the Journals Portal Capes, considering the entire collection of databases. The search was carried out in the period of May 2020, by remote access, with the descriptors: Sars-cov2 OR Covid-19 OR Coronavirus AND Olfactory OR Smell OR Anosmia OR Hyposmia OR Dysosmia OR Dysgeusia. After screening and eligibility, 15 publications were selected. The studies identified mild to severe hyposmia, anosmia, phantosmia and parosmia, associated or not with hypogeusia and ageusia, in prevalence between 22.7 to 88.8% in general. Symptoms usually occur at the onset of the disease (within five days). The main comorbidities were fever, myalgia, fatigue, cough and diarrhea. Olfactory and gustatory symptoms, mainly in the absence of other otorhinolaryngological manifestations, were strongly associated with the diagnosis of COVID-19, highlighting its role as a screening criterion for patients with suspected disease.